Efek Radiasi Sinar Gamma Terhadap Perkecambahan Serbuk Sari dan Pembuahan Cabai Besar - Muhammad Alwi; Eny Yuniaty (Biology Department, Mathematics and natural science, Tadulako University, 2009)
This research aim to to know influence of -ray irradiation sprout of pollen, and also effect to percentage of efficacy of impregnation of hot pepper plant. Result of research indicate that hot pepper plant (LV-2319, LV-2323 have pollen higher viabel generally than hot pepper plant (CK-L, CK-C). This result energy of sprout of pollen and mount impregnation efficacy also become high, that is reach 36,20% (LV-2323) and 28,60% (LV-2319).